Comparison of porosity improvement of silk fibroin membrane using polyethylene glycol and glutaraldehyde for increasing oxygen permeability - Pacharawan Ratanasongtham (2018)
Biomaterial is one of the good candidates for porous membrane preparation according to its environmental friendliness. In this work, the porous membranes of silk fibroin (SF) were prepared by solution casting with the addition of polyethylene glycol (PEG) and glutaraldehyde (GTA) aiming to improve the porosity and oxygen permeability of SF membrane. The conformation of SF was changed from random coil to β sheet form after treatment with MeOH. The interaction existing between SF chains and both PEG and GTA were characterized using Fourier Transform Infrared spectroscopy (FT-IR). The addition of PEG could produce more porosity in the membrane than GTA confirmed by their morphology observed from scanning electron microscopy (SEM). Moreover, the swelling behavior of the SF-PEG and SF-GTA membranes depended on the porous structure of the membrane which directly correlated to their oxygen permeability. The porosity of the SF membranes increased with the increase of PEG and GTA contents up to 40% and 3%w/w, respectively. After that, their porosity decreased as seen through the SEM and water swelling results. In addition, the SF-PEG membrane turned out to have higher degrees of both porosity and oxygen permeability than the SF-GTA membrane which related to its water swelling behavior. © (2013) Trans Tech Publications, Switzerland.